EVIDENCE BASED CASE REPORT (EBCR): PENGARUH AKUPRESUR PADA TITIK LV4 DAN LI4 TERHADAP NYERI PERINEUM SETELAH PERSALINAN PERVAGINAM - Salwa, Putri Dwi (Jurnal Kesehatan Siliwangi, 2024)
Background: The application of acupressure can be used as a non=pharmacological technique for postpartum, acupressure can be applied to various point on the body. One of wivh is the points LV4 and LI4 points, these points are used to treat constipation, pain, swelling, and redness in genital area, as well as pain symptoms related to gynecological problems such as during chilbirth, and primary dysmenorrhea. The application of acupressure can be used as an analgesic technique to reduce pain due to perineal trauma (such as episiotomy and spontaneous rupture). Purpose: The effect of acupressure techniques at the LV4 and LI4 points on perineal suture pain after chilbirth. Method: This journal search method uses keywords, Boolean operators and E-data Based according to predetermined criteria. Result: There was an influence that occurred on the intensity of pain in perineal wounds by providing acupressure techniques two hours after delivery, namely reducing the pain of perineal suture wounds which began using the VAS instrument, namely 8 after 2 hours of intervention to 3. Conclusion: there is an effect on the intensity of pain in perineal wounds by providing acupressure techniques two hours after delivery, namely reducing the pain of perineal suture.